URGENSI DAN FUNGSI PERJANJIAN PERKAWINAN - Eman Sulaiman (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2021)
Marriage agreement is an agreement regarding the property of husband and wife during their marriage which deviates from the principle or pattern established by law. With the marriage agreement, the married life of a married couple will be safe and peaceful. Because, there is no need to worry about the tendency of one party to monopolize or control property in their marital relationship. With a marriage agreement, it will also be easy for them to separate which ones are gono-gini assets and which really become the private property of each partner. The marriage agreement does not only function after the end of the husband-wife marriage period. However, it also serves to provide direction to married couples to heed the agreements they made when they were about to get married, such as an agreement not to commit domestic violence, giving the wife the freedom to continue her education, or the opportunity to take care of the children. Thus, the marriage agreement does not need to be considered taboo because it has multiple functions that will secure their marital or household relationship.